Reagentless Detection of Low-Molecular-Weight Triamterene Using Self-Doped TiO2 Nanotubes - Hudari, Felipe F. [UNESP]; Bessegato, Guilherme G. [UNESP]; Bedatty Fernandes, Flávio C. [UNESP]; Zanoni, Maria V. B. [UNESP]; Bueno, Paulo R. [UNESP] (My University, 2018)
TiO2 nanotube electrodes were self-doped by electrochemical cathodic polarization, potentially converting Ti4+ into Ti3+, and thereby increasing both the normalized conductance and capacitance of the electrodes. One-hundred (from 19.2 ± 0.1 μF cm-2 to 1.9 ± 0.1 mF cm-2 for SD-TNT) and two-fold (from ∼6.2 to ∼14.4 mS cm-2) concomitant increases in capacitance and conductance, respectively, were achieved in self-doped TiO2 nanotubes; this was compared with the results for their undoped counterparts. The increases in the capacitance and conductance indicate that the Ti3+ states enhance the density of the electronic states; this is attributed to an existing relationship between the conductance and capacitance for nanoscale structures built on macroscopic electrodes. The ratio between the conductance and capacitance was used to detect and quantify, in a reagentless manner, the triamterene (TRT) diuretic by designing an appropriate doping level of TiO2 nanotubes. The sensitivity was improved when using immittance spectroscopy (Patil et al. Anal. Chem. 2015, 87, 944-950; Bedatty Fernandes et al. Anal. Chem. 2015, 87, 12137-12144) (2.4 × 106 % decade-1) compared to cyclic voltammetry (5.8 × 105 % decade-1). Furthermore, a higher linear range from 0.5 to 100 μmol L-1 (5.0 to 100 μmol L-1 for cyclic voltammetry measurements) and a lower limit-of-detection of approximately 0.2 μmol L-1 were achieved by using immittance function methodology (better than the 4.1 μmol L-1 obtained by using cyclic voltammetry).